SAT Prep Plus 2023: 5 Practice Tests + Proven Strategies + Online + Video - Kaplan Test Prep (New York Kaplan, 2022)
The Best Practice Five full-length Kaplan practice tests: 2 in the book and 3 online More than 1,500 practice questions with detailed explanations Pre-quizzes to help you figure out what you already know and what you can skip Mixed practice quizzes after every chapter to assess how much you've learned A practice question at the beginning of each lesson to help you quickly identify its focus; dedicated practice questions after every lesson to test your comprehension Expert scoring, analysis, and explanations online for two official College Board SAT Practice Tests Efficient Strategy "On Test Day" strategy notes in every math chapter to help you remember that the SAT math test is primarily a strategy test. "Reflect" pages that help you evaluate your comfort level with the topics after completing each chapter and make a plan for improving before the test. Online study-planning tool helps you target your prep no matter how much time you have before the test. Kaplan's expert strategies for each test section, including special techniques for the optional essay. Expert Guidance We know the test: Our learning engineers have put tens of thousands of hours into studying the SAT, and use real data to design the most effective strategies and study plans. Kaplan's books and practice questions are written by veteran teachers who know students-every explanation is written to help you learn.
Keywords: SAT